A case report on rare ultrasound finding of spontaneous chorioamniotic membrane separation - Kamble, Pradnya Digambar; Aupont, Jean; Fatima, Maryam; Ahmed , Mustafa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The separation of the chorion and amnion before 14 weeks of gestation is physiologically normal. The amnion and chorion usually fuse between 14 and 16 weeks, and any chorioamniotic separation (CAS) that persists after 16 weeks is uncommon and anomalous. CAS can occur spontaneously or after an intrauterine intervention such as amniocentesis where it may be detected on follow-up ultrasound. Another cause of chorioamniotic membrane separation (CAMS) can be chromosomal abnormalities which present with the absence or delayed fusion of the two layers. It is associated with poor perinatal outcomes such as preterm delivery, preterm prelabour rupture of membranes (PPROM) and amniotic band syndrome. As cases of spontaneous CAMS (sCAMS) are exceptionally rare, perinatal outcomes associated with it are ambiguous. This poses a difficulty for clinicians who are managing the case to determine appropriate antepartum care. It also hinders the clinician’s ability to counsel patients. We hope our case report helps in better recognition of the abnormality and encourages more reporting and studies of similar cases to be able to have a better understanding of the full implications of such sonographic findings. Moreover, increased reporting will help obstetricians to mitigate the fetal and maternal risks associated with sCAMS.